Date Mucilage as Co-Polymer in Metformin-loaded Microbeads for Controlled Release (2019)
Mucilage from the fruit of the date palm (Phoenix dactylifera) was characterized and evaluated for use as a polymer in controlled release metformin-loaded microbeads. Metformin-loaded (1% w/w) microbeads were formed by the ionotropic gelation method using blends (2% w/v) of date mucilage: sodium alginate in varying concentrations (20:80 C4, 25:75 C3, 33:67 C2, 50:50 C1) using zinc chloride (10% w/v) as a crosslinking agent. Bead size and morphology, swelling index, entrapment efficiency and release properties were then measured. The dissolution profiles were fitted to kinetic equations to determine the kinetics and mechanisms of drug release while the similarity factor, ƒ2 was used to determine formulations with similar drug release patterns. The results showed that the date mucilage had crude fat content of 2.5%. The microbeads formed were spherical with bead sizes ranging from 0.44 to 1.99 mm except for the one prepared using blend C4 which was ellipsoidal. Drug entrapment efficiency ranged between 25.0 and 91.1%w/w with alginate alone giving the least entrapment. Microbeads formulated with blends C2 and C3 had the slowest dissolution rates at t15 < 9% in 240 minutes. C3, however, had a higher entrapment efficiency and was considered the optimum formulation. All microbead formulations fitted the Korsmeyer-Peppas’ model with super case II transport mechanism except for the one made of sodium alginate alone, which had an anomalous (non-Fickian) diffusion. Secondary parameters of the Korsmeyer-Peppas’ model showed that microbead formulations C2 and C3 provided controlled release for longer than 24 hours. Similarity factor, ƒ2 showed comparable release profiles between C2 and C3 (ƒ2=94.2). This study shows that mucilage from the date fruit could potentially be used as a polymer in the formulation of controlled release metformin-loaded microbeads.